BRST symmetry and fictitious parameters - Nogueira, A. A.; Pimentel, B. M. [UNESP] (American Physical Society (APS), 2017)
Our goal in this work is to present the variational method of fictitious parameters and its connection with the Bechi-Rouet-Stora-Tyutin (BRST) symmetry. First, we implement the method in QED at zero temperature and then we extend the analysis to generalized QED at finite temperature. As we see the core of the study is the general statement in gauge theories at finite temperature, assigned by Tyutin work, that the physical degrees of freedom do not depend on the gauge choices, covariant or not, due to BRST symmetry.